The Rise and Fall of the Hasanwayhid Barzikani Dynasty (941-1015): Mapping Territories and Unraveling the Causes and Contributing Factors of Its Collapse - Nariman Abdalla Ali (International Journal of Islamic Khazanah, 2024)
Â This research significantly contributes to our understanding of the Emirate of Hasanwayhid Barzikani's rise and fall within the Abbasid Caliphate. The study unveils the intricate factors that shaped the emirate's destiny by meticulously mapping its geographical extent and employing an analytical-critical approach. The identification of key contributors, such as persistent tensions with the Buyids, internal rivalries, and the geopolitical context of its proximity to the Abbasid Caliphate's center, enriches historical discourse. Furthermore, the research underscores the impact of wars of attrition and internal conflicts on the emirate's stability. Methodologically, the thorough examination of primary and secondary sources enhances the reliability and depth of the findings. Ultimately, this research not only sheds light on the complex dynamics of Hasanwayhid Barzikani's existence and demise but also underscores the broader significance of considering multifaceted political, military, and socio-cultural factors in comprehending the dynamics of emirates during this historical period.